6(x-6)+4=8x-13

Simple and best practice solution for 6(x-6)+4=8x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-6)+4=8x-13 equation:


Simplifying
6(x + -6) + 4 = 8x + -13

Reorder the terms:
6(-6 + x) + 4 = 8x + -13
(-6 * 6 + x * 6) + 4 = 8x + -13
(-36 + 6x) + 4 = 8x + -13

Reorder the terms:
-36 + 4 + 6x = 8x + -13

Combine like terms: -36 + 4 = -32
-32 + 6x = 8x + -13

Reorder the terms:
-32 + 6x = -13 + 8x

Solving
-32 + 6x = -13 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-32 + 6x + -8x = -13 + 8x + -8x

Combine like terms: 6x + -8x = -2x
-32 + -2x = -13 + 8x + -8x

Combine like terms: 8x + -8x = 0
-32 + -2x = -13 + 0
-32 + -2x = -13

Add '32' to each side of the equation.
-32 + 32 + -2x = -13 + 32

Combine like terms: -32 + 32 = 0
0 + -2x = -13 + 32
-2x = -13 + 32

Combine like terms: -13 + 32 = 19
-2x = 19

Divide each side by '-2'.
x = -9.5

Simplifying
x = -9.5

See similar equations:

| 18x-6+8x-4=120 | | 60n-16+29=67+59n | | 7x-37=3x+23 | | 4x-4x-16= | | -2(14-3p)=7(p-10) | | 5m+7-42= | | 5u^2-18u=-9 | | 6n-6=2n+20 | | 4-3x=9+x-5x | | .75=0.4p+100 | | 0.25+y=225 | | 1.66x-9=61x-201 | | 3m=2(4+x)salveforx | | 5x-3*5=15 | | 9x-40=7x-37 | | (x+14)+3x=180 | | 19-3n=13 | | -37+6x=19+2x | | 3p+5q=7 | | 6+5g=3g+20 | | 4x-10=7x-9 | | 10=0.83(n+6) | | 2-(-2)s=6 | | -x-18=36 | | 0.5x+.01x+12+1x-5=9.96 | | 3d+4(-3)=11 | | 2661=63+63(n-1) | | x^2-kx+9=y | | 4x+3a=bx+2.5a-5 | | 5(x+3)-2=2x+9 | | 6x+8x-42=84-7x | | v-7.5=3.4 |

Equations solver categories